FDTD Analysis of EM Field Effected by the Motion of Source and Vehicle - S., Sahrani; T., Akata; M., Kuroda (IEEE, 2014)
A numerical technique for the analysis of the electromagnetic (EM) fields by moving sources and moving bodies can be significantly important for the realization of next generation nano-electronic devices particularly for mobile communication system. However, most of the analysis were primarily focused on the stationary source. We have previously proposed the Overset Grid Generation method combined with the FDTD method for the analysis of the EM field with moving body. In this paper, this technique is applied for the analysis of the EM field in a street cross section from moving vehicle and moving source. Here, the Doppler effect is observed by the moving vehicle and moving source.